Extended chondrule formation intervals in distinct physicochemical environments: Evidence from Al-Mg isotope systematics of CR chondrite chondrules with unaltered plagioclase. (1st September 2019) - Tenner, Travis J.; Nakashima, Daisuke; Ushikubo, Takayuki; Tomioka, Naotaka; Kimura, Makoto; Weisberg, Michael K.; Kita, Noriko T.
Abstract: Al-Mg isotope systematics of twelve FeO-poor (type I) chondrules from CR chondrites Queen Alexandra Range 99177 and Meteorite Hills 00426 were investigated by secondary ion mass spectrometry (SIMS). Five chondrules with Mg#'s of 99.0–99.2 and Δ 17 O of −4.2‰ to −5.3‰ have resolvable excess 26 Mg. Their inferred ( 26 Al/ 27 Al)0 values range from (3.5 ± 1.3) × 10 −6 to (6.0 ± 3.9) × 10 −6 . This corresponds to formation times of 2.2 (−0.5/+1.1) Myr to 2.8 (−0.3/+0.5) Myr after CAIs, using a canonical ( 26 Al/ 27 Al)0 of 5.23 × 10 −5, and assuming homogeneously distributed 26 Al that yielded a uniform initial 26 Al/ 27 Al in the Solar System. Seven chondrules lack resolvable excess 26 Mg. They have lower Mg#'s (94.2–98.7) and generally higher Δ 17 O (−0.9‰ to −4.9‰) than chondrules with resolvable excess 26 Mg. Their inferred ( 26 Al/ 27 Al)0 upper limits range from 1.3 × 10 −6 to 3.2 × 10 −6, corresponding to formation >2.9 to >3.7 Myr after CAIs. Al-Mg isochrons depend critically on chondrule plagioclase, and several characteristics indicate the chondrule plagioclase is unaltered: (1) SIMS 27 Al/ 24 Mg depth profile patterns match those from anorthite standards, and SEM/EDS of chondrule SIMS pits show no foreign inclusions; (2) transmission electron microscopy (TEM) reveals no nanometer-scale micro-inclusions and no alteration due to thermal metamorphism; (3) oxygen isotopes of chondrule plagioclase match those of coexisting olivine and pyroxene, indicating a low extent of thermal metamorphism; and (4) electron microprobe data show chondrule plagioclase is anorthite-rich, with excess structural silica and high MgO, consistent with such plagioclase from other petrologic type 3.00–3.05 chondrites. We conclude that the resolvable ( 26 Al/ 27 Al)0 variabilities among chondrules studied are robust, corresponding to a formation interval of at least 1.1 Myr. Using relationships between chondrule ( 26 Al/ 27 Al)0, Mg#, and Δ 17 O, we interpret spatial and temporal features of dust, gas, and H2 O ice in the FeO-poor chondrule-forming environment. Mg# ≥ 99, Δ 17 O ∼ −5‰ chondrules with resolvable excess 26 Mg initially formed in an environment that was relatively anhydrous, with a dust-to-gas ratio of ∼100×. After these chondrules formed, we interpret a later influx of 16 O-poor H2 O ice into the environment, and that dust-to-gas ratios expanded (100× to 300×). This led to the later formation of more oxidized Mg# 94–99 chondrules with higher Δ 17 O (−5‰ to −1‰), with low ( 26 Al/ 27 Al)0, and hence no resolvable excess 26 Mg. We refine the mean CR chondrite chondrule formation age via mass balance, by considering that Mg# ≥ 99 chondrules generally have resolved positive ( 26 Al/ 27 Al)0 and that Mg# < 99 chondrules generally have no resolvable excess 26 Mg, implying lower ( 26 Al/ 27 Al)0 . We obtain a mean chondrule formation age of 3.8 ± 0.3 Myr after CAIs, which is consistent with Pb-Pb and Hf-W model ages of CR chondrite chondrule aggregates. Overall, this suggests most CR chondrite chondrules formed immediately before parent body accretion.